A novel method for generating glutamatergic SH-SY5Y neuron-like cells utilizing B-27 supplement - Martin, Emily-Rose; Gandawijaya, Josan; Oguro-Ando, Asami (Frontiers in Pharmacology, 2022)
The human SH-SY5Y neuroblastoma cell line is widely used in neuroscience research as a neuronal cell model. Following differentiation to a neuron-like state, SH-SY5Y cells become more morphologically similar to neurons and form functional synapses. Previous studies have managed to differentiate SH-SY5Y cells towards cholinergic, dopaminergic and adrenergic fates. However, their application in disease modeling remains limited as other neuronal subtypes (e.g., glutamatergic, GABAergic) are also implicated in neurological disorders, and no current protocols exist to generate these subtypes of differentiated SH-SY5Y cells. Our study aimed to evaluate the use of B-27, a supplement commonly used in neuronal culture, for SH-SY5Y maintenance and differentiation. To evaluate the proliferative capacity of SH-SY5Y cells cultured in B-27, we performed growth curve analyses and used qRT-PCR to track changes in cell cycle progression. SH-SY5Y cells cultured in FBS or under serum-starved conditions were used as controls. We observed that SH-SY5Y cells show reduced growth rate following 4-day exposure to B-27 accompanied by decreased CDK6 and CDK1 expression, suggesting B-27 induces a quiescent state in SH-SY5Y cells. Importantly, this reduced growth rate was not due to increased apoptosis. As cell cycle exit is associated with differentiation, we next sought to determine the fate of SH-SY5Y cells cultured in B-27. B-27-cultured SH-SY5Y cells show changes in cell morphology, adopting pyramidal shapes and extending neurites, and upregulation of neuronal differentiation markers (GAP43, TUBB3 and SYP). B-27-cultured SH-SY5Y cells also show increased expression of glutamatergic markers (GLUL and GLS). These findings suggest that B-27 may be a non-toxic inducer of glutamatergic SH-SY5Y differentiation.